ArNMeCH(SiMe3)2: a useful precursor of formal α-aminoalkyl diradicals in visible-light-mediated homo- and hetero-diaddition with alkenes. Issue 54 (4th June 2020) - Liu, Shunfa; Yang, Yufan; Gao, Lu; Song, Zhenlei
Abstract : ArNMeCH(SiMe3 )2 has been developed as a useful precursor of a formal α-aminoalkyl diradical in visible-light-mediated homo-diaddition with two identical alkenes in one-pot, or hetero-diaddition with two different alkenes via a sequential operation. Abstract : ArNMeCH(SiMe3 )2 has been developed as a useful precursor of a formal α-aminoalkyl diradical in Ru(bpy)3 Cl2 -catalzyed addition with alkenes under visible-light-mediated photoredox conditions. This approach leads to homo-diaddition with two identical alkenes in one-pot, or hetero-diaddition with two different alkenes via a sequential operation.